The approaches to prevention and therapy of cardiovascular disorders in children with chronic bronchopulmonary pathology - G. O. Lezhenko; О. Ye. Pashkova (Zaporožskij Medicinskij Žurnal)
The purpose of this study was to develop and evaluate the algorithm for cardiovascular disorders prevention and therapy effectiveness in children with chronic bronchopulmonary pathology.